Daya Tutur Metafora Lirik Lagu Populer (Kajian Pragmatik) - M. Hermintoyo M. Hermintoyo (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
Communicating can be done with any media as needed and function, one of them communication through song lyrics. Song lyrics are created to have a specific purpose in addition to being an aesthetic creative means by using figurative language in the form of metaphors can also be a means of speaking with the audience. Speech done is empowered speechless illocution and perlokusi. Ilocution is the act of doing something. The act of illocution is a speech act that contains the purpose and function or the power of speech. The question posed related to the act of illocution is For what the speech was done. While Perlokusi speech that has the effect or influence power. The effect or power of the speech may be caused by the speaker intentionally or unintentionally. The study used is a pragmatic study. The data is taken from the lyrics of Indonesia's popular metaphorical song.